Pertumbuhan dan Produksi Tanaman Jagung (Zea mays L.) Akibat Pemberian Kompos Ela Sagu dan Pupuk Organik Cair (POC) pada Tanah Ultisol - Elizabeth Kaya; Adelina Siregar; Diane M.Y. Matulessy; Masitta Hasan (Universitas Pattimura, 2016)
The purpose of this study is to determine the growth and yield of maize (Zea mays L) as responses of organic fertilizer sago palm waste compost and liquid organic fertilizer (LOF) on Ultisols. The research was conducted on the field in the village of Telaga Kodok. The treatments were carried out in a factorial experiment using randomized block design in which the sago palm waste compost consisted of 4 dose levels: 0, 30, 45, and 60 tons/Ha and liquid organic fertilizer (LOF) was composed of 3 dose levels: 0, 10, and 20 mL/L solution which is repeated three times, so that there were 36 treatment combinations. The results showed that the application of sago palm waste compost and LOF independently promote plant growth (height and stem diameter) of corn, as well as the production of plant (length, diameter, and weight of cobs) of Corn. While the sago palm waste application together with LOF could improve corn dry seed weight as much as 121.33 g per plant or 5.8 ton/Ha on soil Ultisol.